Cuties, Creams and Cushing - Sakaleshpur Kumar, Vikram; Sarji Rudrappa, Dhananjaya; Ravindran, Thejaswini; Srinivas, Girish; Gowda, Shivaraj (Belgian Journal of Paediatrics, 2023)
Prolonged use of corticosteroids can lead to serious side effects, including Cushing’s Syndrome (CS), a disorder caused by abnormally high levels of free plasma glucocorticoids, and hypothalamo-pituitary axis suppression. The cause of CS may be either natural production or external administration of steroids. Iatrogenic CS is most commonly caused by oral or injectable medications and rarely by topical application. The absorption rate is higher with transcutaneous than with topical application. Only few cases of CS after topical application have been reported. We present the case of a 2-month-old girl who developed CS due to prolonged use of topical steroids.